Antibodies specific for measles virus envelope antigens and autoantibodies in patients with chronic active hepatitis. Issue 11 (November 1985) - Shirodaria, P V; McMillan, S A; Callender, M E; Haire, M; Fleming, E; Merrett, J D; Fulton, T T
Abstract : Distinctly increased levels of antibodies to measles virus envelope antigens haemolysin and haemagglutinin were found in the sera of patients with chronic active hepatitis compared with a normal control group, using immunofluorescence and functional tests. Similarly, a higher incidence of smooth muscle antibody of both IgG and IgM classes was observed in the patients and an important correlation was found between haemolysin antibodies specific for measles virus and smooth muscle antibody of IgG and IgM classes. In contrast, there was no such correlation between the virus specific haemolysin antibodies and antinuclear antibodies. The increased levels of antibodies to measles virus envelope antigens and of autoantibodies may reflect defects in immunoregulation rather than persistent infection with measles virus.